Luminescence properties of Yb3+-Tb3+ co-doped amorphous silicon oxycarbide thin films - Flores L.F. (2019)
This work was supported by the Peruvian science foundation CIENCIACTIVA of CONCYTEC and DAAD-CONCYTEC project (2017–2019). The Research Management Office (DGI) of the the Pontificia Universidad Católica del Perú (PUCP) project 492-2017. The research activity was performed in the framework of the doctoral scholarship of L. F. Flores under the contract number 236-2015-FONDECYT. The authors are also thankful to the Center of Materials Characterization (CAM) and the Institute of Corrosion and Protection (ICP) of the PUCP for the EDX, PL and FTIR measurements.